Hallucinations in Older Adults: A Practical Review. (8th July 2020) - Badcock, Johanna C; Larøi, Frank; Kamp, Karina; Kelsall-Foreman, India; Bucks, Romola S; Weinborn, Michael; Begemann, Marieke; Taylor, John-Paul; Collerton, Daniel; O'Brien, John T; El Haj, Mohamad; Ffytche, Dominic; et al.
Abstract: Older adults experience hallucinations in a variety of social, physical, and mental health contexts. Not everyone is open about these experiences, as hallucinations are surrounded with stigma. Hence, hallucinatory experiences in older individuals are often under-recognized. They are also commonly misunderstood by service providers, suggesting that there is significant scope for improvement in the training and practice of professionals working with this age group. The aim of the present article is to increase knowledge about hallucinations in older adults and provide a practical resource for the health and aged-care workforce. Specifically, we provide a concise narrative review and critique of (1) workforce competency and training issues, (2) assessment tools, and (3) current treatments and management guidelines. We conclude with a brief summary including suggestions for service and training providers and future research.